Membentuk Citra Perusahaan Hijau Melalui Sikap Hijau Dan Pengetahuan Ekologi Dari Konsumen Air Minum Dalam Kemasan Aqua - Savitri Siswono; Sri Widyastuti (JRB-Jurnal Riset Bisnis, 2018)
In the framework of green marketing, environmental management is a strategic tool not only increases control and reduces environmental impact but also develops business opportunities for the company. Companies need to observe green attitudes, as it is important to predict consumer behavior. Green attitudes as a kind of eco-friendly behavior that consumers do to express their concern for the environment. Not all companies have enough capability to market their green products to consumers. Environmental attitude refers to mental readiness that directly affects the consumer's response to the environment. This type of eco-friendly behavior that consumers do to express their concern for the environment. In addition, the existence of consumer ecological knowledge is a variable that can predict to be able to form a company's green image. The findings in this study revealed that green attitudes and ecological knowledge proved to have an effect on the formation of the image of green companies.